ZAMONAVIY TA’LIMDA INNOVATSION TEXNOLOGIYALAR VA ULARNING TA’LIM SAMARADORLIDAGINI OSHIRISHDAGI O’RNI - G.Qurbonova (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article describes the essence of modern education, comprehensive coverage of pedagogic activity, professional skills of future teachers, creative approach to the lesson, and the use of new forms and methods of teaching.